2012
DOI: 10.1074/jbc.m112.359950
|View full text |Cite
|
Sign up to set email alerts
|

Fenretinide Prevents Lipid-induced Insulin Resistance by Blocking Ceramide Biosynthesis

Abstract: Background:Fenretinide, an in-trial chemotherapeutic, improves insulin sensitivity in mice and humans. Results: Fenretinide reduces Des1 expression and prevents ceramide accumulation, while protecting against lipid-induced insulin resistance. Conclusion: Fenretinide decreases ceramide biosynthesis, and increases levels of dihydroceramides, thus preserving insulin responsiveness. Significance: These data suggest that Des1 may be a viable therapeutic target for normalizing glucose homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
110
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(121 citation statements)
references
References 36 publications
10
110
1
Order By: Relevance
“…3H ). These data support the results from previous studies, which showed that fenretinide is a stimulator of SPT (13)(14)(15) but an inhibitor of DEGS ( 16,17 ).…”
Section: Fenretinide Inhibited the De Novo Synthesis Of Ceramide Aftesupporting
confidence: 92%
See 3 more Smart Citations
“…3H ). These data support the results from previous studies, which showed that fenretinide is a stimulator of SPT (13)(14)(15) but an inhibitor of DEGS ( 16,17 ).…”
Section: Fenretinide Inhibited the De Novo Synthesis Of Ceramide Aftesupporting
confidence: 92%
“…Early studies of fenretinide supported the hypothesis that fenretinide increased the de novo synthesis of ceramide by stimulating SPT (13)(14)(15). However, later studies ( 16,17 ) confi rmed that fenretinide increased dhCer, not ceramide levels. The later studies demonstrated that fenretinide was a potent inhibitor of DEGS ( 16,17 ).…”
Section: Quantitative Real-time Pcrmentioning
confidence: 95%
See 2 more Smart Citations
“…Blockade of Des1 produces an increase in dihydroceramides (dhCers), which have emerged as bioactive lipids and the target of several drugs ( 34 ), including fenretinide. Several studies have shown that cells respond to fenretinide treatment with a robust production of dhCers (35)(36)(37)(38)(39)(40)(41)(42)(43)(44), and that this increase induces autophagy ( 45,46 ). Furthermore, experimental evidence exists on the connection between resistance to fenretinide and increased S1P production ( 38,44 ) due to an increased SK activity and SK1 mRNA and protein levels ( 38 ).…”
Section: Des1 Enzyme Assaymentioning
confidence: 99%